Effect of intercropping on yields of corn with different relative maturities and Palisadegrass - Crusciol, Carlos Alexandre Costa [UNESP]; Nascente, A. S.; Mateus, G. P.; Borghi, E.; Leles, E. P. [UNESP]; Santos, N. C B (Wiley, 2013)
Intercropping corn (Zea mays L.) with palisadegrass [Brachiaria brizantha (Hochst. ex A. Rich) Stapf] can result in high amounts of residue and improve nutrient cycling. Long-season corn hybrids will live longer, competing with palisadegrass, which may reduce both corn and forage biomass yields. This study, conducted in the state of São Paulo, Brazil, had the objective of evaluating nutrient concentration and yield of corn hybrids with different maturity ratings as affected by intercropped palisadegrass as well as forage dry matter production. Te experimental design was randomized blocks with a factorial arrangement of eight treatments consisting of two cropping systems (corn alone and intercropped with palisadegrass) and four corn hybrids (105-, 121-, 132, and 144-d relative maturity). Compared with corn grown alone, intercropping treatments resulted in corn grain yields of 107% (105-d hybrid) to 71.7% (144-d hybrid). In the corn-alone system, the 132- and 144-d corn hybrids provided the highest corn yields (9581 and 9606 kg ha-1, respectively). Corn yield was similar between the single-crop and intercrop systems when using 105-, 121-, and 132-d hybrids. Intercropping with the 144-d hybrid reduced forage production (6619 kg ha-1) and quality of palisadegrass (86 g kg-1 of crude protein) compared with the other hybrids. Te intercropping system with the 132-d hybrid allowed both the highest corn grain (8860 kg ha-1) and palisadegrass (8256 kg ha-1) yields. Therefore, intercropping palisadegrass with the earlier (105-, 121-, and 132-d) corn hybrids is a viable option for crop-livestock integration because it did not affect either corn or palisadegrass yield. © 2013 by the American Society of Agronomy, 5585 Guilford Road, Madison, WI 53711. All rights reserved.